Influência do fotoperíodo sobre o relógio molecular e o eixo somatotrópico de alevinos da tilápia-do-nilo (Oreochromis niloticus) - Santos, Marcia Dantas dos (2017)
The most of living organisms have a habitual cycle from which they perform all their activities. These are generated internally by the molecular clock and synchronized by the abiotic factors to a period around 24 hours. For fish, the photoperiod is one of the environmental synchronizers that has a great influence on the molecular clock, coordinating environmental factors with its physiology. One of the systems that seems to be under the influence of the endogenous molecular clock is the endocrine system, precisely the somatotropic axis. To investigate the relationship between the clock and the endocrine system, we aimed to analyze the expression of a molecular clock gene, clock1a, and the gene of the somatotropic axis, gh, of Nile tilapia (Oreochromis niloticus) fingerlings when exposed to photoperiods from 12h: 12h light: dark (C: E) and 24h (C: C); And to verify the influence of the photoperiod on the length, mass, body growth and condition factor. The fingerlings were kept in the photoperiod for 52 days and biometry was performed on days 0, 7, 22, 37 and 52. At the end of the exposure, the animals were sacrificed and the brain was extracted for quantification of gene expression. Regarding the length, we observed no differences as a function of the photoperiod, except at times 22 and 37 (days), whose averages were 4.95 ± 0.36, 4.75 ± 0.41 and 6.65 ± 0.66 , 6.39 ± 0.68cm for C: C and C: E, respectively. Regarding body mass, difference was only observed on day 7, with 1.08 ± 0.23 C: C and 0.98 ± 0.23g C: E, respectively. Regarding the growth, no significant differences between treatments were observed, except between day 7 and 37 that presented a differentiated growth between the photoperiods. Regarding the condition factor, the data did not reveal significant differences. The analyzed genes did not present a circadian pattern of expression, but the clock1a gene showed differences in their daily levels, that is, between the sampling points for the two photoperiods. Also, larger expression oscillations were also observed for the C: E photoperiod for the clock1a gene. The gh, in turn, did not present a biological rhythm as well as absence of differences between the times. Finally, the possibility of the correlation between the genes mentioned above in their respective photoperiod conditions was tested. However, the resulting scores were highly distant from any correlation. In summary, exposure to photoperiods did not significantly interfere with the biometric variables and between the molecular clock genes and the somatotropic axis.